Lubrication subjected to effects of electric and magnetic fields: recent research progress and a generalized MEMT-field Reynolds equation - Wang, Xiaoman; Wang, Q. Jane; Ren, Ning; England, Roger (Frontiers in Mechanical Engineering, 2024)
Electric and magnetic fields have been used in various ways to enhance the performance of lubrication systems. The presence of these fields can significantly change the properties of lubricants. The rapid adoption of electric vehicles (EVs) has presented new lubrication-related challenges due to the presence of electric current. There is an urgent need for an in-depth study of lubrication systems subjected to such fields. This paper highlights recent research works on several key areas of lubrication involving electric or magnetic fields, which are:1) electric double layer in lubrication, 2) electrorheological fluids, 3) magnetorheological fluids, 4) ferrofluids, and 5) typical fluids used in the current EVs and typical surface failures of bearing components in EVs. Commonly used lubricants in each area are reviewed; lubrication mechanisms and related mathematical models are summarized; methods for and results from numerical analyses and experimental explorations are discussed; and common features of lubrications in different fields are explored. Based on the current research progress in these fields and the classic generalized Reynolds equation, a generalized all-field Reynolds equation is proposed to describe the aforementioned lubrication scenarios and the effects of coupled mechanical, thermal, electric and magnetic fields.